Effectiveness of sucking ice cubes to prevent and reduce the severity of oral mucositis: Efektivitas mengisap es batu untuk mencegah dan mengurangi keparahan mucositis mulut - Yessy Novianti; Tenny Setiani Dewi (Makassar Dental Journal PDGI Makassar, 2023)
Oral mucositis is an inflammation that occurs in the oral mucosa due to side effects of cancer therapy in the form of chemotherapy, radiotherapy, and chemoradiotherapy. The condition of severe oral mucositis can worsen the prognosis of cancer treatment and reduce the patient's quality of life. One method to reduce the severity of oral mucositis is cryotherapy. The purpose of this systematic review is to review the effectiveness of oral cryotherapy using the ice cube method in preventing and reducing the severity of oral mucositis. This review was conducted using PRISMA guidelines. Article searches were conducted using five electronic databases, namely PubMed, Science Direct, Cochrane, Scopus and Springer Link for articles published 2017-2022 using specific keywords. The criteria were limited to randomized controlled trial in hu-man, full text, and in English only. The results were the incidences of oral mucositis, the severity and pain scores in patients. The study quality graded using the Modified Jadad Scale. There were seven articles that met the eligibility criteria for analysis. It is concluded that the majority of studies prove that oral cryotherapy using ice cubes is effective in preventing and reducing the severity of oral mucositis.